Careers guidance in context - Gothard, Bill.; Sage eBooks (London : SAGE, 2001)
'Careers Guidance in Context' is designed to develop understanding of the social, economic and political factors that shape both the labour market and careers guidance as an occupation in itself.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Vocational guidance; Vocational guidance -- Philosophy; Career education; Electronic books